2017
DOI: 10.1016/j.atmosenv.2017.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of biogenic contributions to ozone formation over the United States

Abstract: 1 2 Vegetation is the leading emitter of volatile organic compounds (VOC), a key ingredient for ozone formation. The contribution of biogenic VOC (BVOC) emissions to regional ozone formation needs better quantification so that air quality regulators can effectively design emission control strategies. One of the key uncertainties for modeling BVOC emissions comes from the estimation of photosynthetically active radiation (PAR) reaching canopy. Satellite insolation retrieval data provide an alternative to progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Further, higher biogenic VOCs emissions due to the presence of vegetation in Northern Beijing can favor O 3 formation [80]. On the other hand, the higher NOx concentrations observed in Southern Beijing favor O 3 titration [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Further, higher biogenic VOCs emissions due to the presence of vegetation in Northern Beijing can favor O 3 formation [80]. On the other hand, the higher NOx concentrations observed in Southern Beijing favor O 3 titration [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…BVOCs play crucial roles in both formation and removal processes of ozone (Calfapietra 35 et al, 2013). Comparison between MEGAN and another widely used biogenic emission model, the Biogenic Emission Inventory System (BEIS) indicated that the influence of biogenic emission models on ozone simulation results is among the highest over all the model inputs (Kim et al, 2017;Zhang et al, 2017). The potential influence of biogenic emissions on aerosol modelling results is more complicated.…”
Section: Estimated Isoprene and Monoterpenes Emissions In France Basementioning
confidence: 99%
“…Spatial distribution of isoprene emissions seems to be similar between the two models, qualitatively, except in low emission areas with BEIS where MEGAN shows much higher emission, relatively ( Figure 5). In the United States, a similar pattern that led to gross overestimation of isoprene concentrations was reported for MEGAN, while BEIS3 had much less overestimation [49,50]. As introduced in previous sections, among the biogenic VOCs, isoprene reacts rapidly with hydroxyl radicals in the atmosphere, thereby significantly contributing to ozone concentrations [48].…”
Section: Emissions and Cmaq Model Performancementioning
confidence: 65%